EFEKTIVITAS PELATIHAN MENGGUNAKAN BLENDED LEARNING : LITERATUR REVIEW - Rahmadeni, Asfri Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Improving the quality of human resources is an important issue in training. Currently, the blended learning model is a widely used training approach that is expected to improve the quality of training. The aim is to analyze the blended learning model as a training strategy in training institutions. This research method uses a literature review research design. The database used is Google Scholars, Science Direct, and published in the range of 2017-2023. Blended learning is a learning approach that integrates traditional face-to-face learning and distance learning using online learning resources. Literature studies show that blended learning training is effective in improving participants' knowledge and skills. Although there are barriers such as limited facilities and internet networks, careful planning and adequate infrastructure can increase the effectiveness of blended learning training. Evaluation of the learning model is also important to continuously improve and enhance its effectiveness.Keywords: Blended Learning, Pelatihan Daring